PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA BIDANG KEPERAWATAN TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT UMUM DAERAH ANUNTALOKO KABUPATEN PARIGI MOUTONG - I Kadek Wartana (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2019)
This study aims to: (1) to analyze how much the partial effect of head of nursing transformational leadership style on the nurses performance in Anuntaloko general hospitals on Parigi Moutong district; (2)to analyze how much the simultaneous effect of head of nursing transformational leadership style on the nurses performance in Anuntaloko general hospitals on Parigi Moutong district. The theory oftransformational leadership style used on Bass, et al (2003), while the nurses' performance used from Bernadin and Russel (2003). This type of research is explanatory research with cross sectional method. The population was 255 nurses in Anuntaloko general hospitals on Parigi Moutong District, while the total sample of 70 nurses with cluster sampling technique of random sampling. Data were analyzed using multiple linear regression. The results showed that; (1) The Partial effect of transformational leadership style head the field of nursing and nurse's performance in Anuntaloko hospital on Parigi Moutong District shows that individualized consideration variables most affect the nurses performance, where the t value (4,377) is greater than t table (1,669). (2) The effect to simultaneously show the overall variable transformational leadership style chief nursing significant effect on the nurses performance in Anuntaloko hospital on Parigi Moutong District, where the value of F count larger than F table with R value of 0,345, which means the level of influence of the independent variable (X ) with the dependent variable (Y) is in the interval from 0,20 to 0,399, which means that there is an influence that is